2019
DOI: 10.21037/atm.2019.06.77
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen prevents articular cartilage destruction in a mouse model of AMPK deficiency via ERK-mTOR pathway

Abstract: Background: To investigate the mechanism underlying the chondroprotective effect of estrogen in AMPactivated protein kinase (AMPK) deficiency mice. Methods: Female cartilage-specific AMPKα double knockout (AMPKα cDKO) mice were generated and subjected to ovariectomy (OVX). The model of osteoarthritis (OA) was induced by destabilization of medial meniscus (DMM). Histopathological changes were evaluated by using OARSI scoring systems. Autophagy changes were analyzed by immunofluorescence staining. Human chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
1
21
2
Order By: Relevance
“…In this regard, it is possible that estrogen may exert a compensatory effect for AMPKα1 deletion. For example, previous studies reported that double global genetic deficiency of AMPKα1 and AMPKα2 in female mice did not affect the inflammatory process of osteoarthritis; whereas estrogen prevented articular cartilage destruction (35,36). Since in our study male and female H-AMPKα1 WT mice exhibited similar organ injury and outcomes after sepsis, we speculate that the differential hormonal milieu between male and female may, indeed, result in a diversification of mitochondria quality control during acute stress only in condition of dysregulation of AMPKα1 and the level of expression per se of this enzyme is most likely a key element for sex-dependent switch of metabolic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is possible that estrogen may exert a compensatory effect for AMPKα1 deletion. For example, previous studies reported that double global genetic deficiency of AMPKα1 and AMPKα2 in female mice did not affect the inflammatory process of osteoarthritis; whereas estrogen prevented articular cartilage destruction (35,36). Since in our study male and female H-AMPKα1 WT mice exhibited similar organ injury and outcomes after sepsis, we speculate that the differential hormonal milieu between male and female may, indeed, result in a diversification of mitochondria quality control during acute stress only in condition of dysregulation of AMPKα1 and the level of expression per se of this enzyme is most likely a key element for sex-dependent switch of metabolic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK consists of a catalytic subunit (α 1, α2) and two regulatory subunits β (β1 and β2) and γ (γ1, γ2, and γ3). AMPK regulated variety of biochemical pathways, which control the signal of cellular energy metabolism, whereas its dysfunction is associated with many human diseases (Ge et al, 2019). mTOR is present in both mTORC1 and mTORC2 complexes and has a negative regulatory effect on autophagy.…”
Section: Tan Iia Induces Tumor Cell Autophagymentioning
confidence: 99%
“…However, the relationship between autophagy and the chondrogenic differentiation of SMSCs needs to be explored in further experiments. Decreased autophagy-related gene expression has been observed in damaged chondrocytes, and enhanced autophagy can slow the pathological progression of osteoarthritis [ 25 , 26 ]. In addition, autophagy deficiency may affect the growth plate chondrocytes, leading to cartilage development delays [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%